Relações interpessoais na organização hospitalar: um estudo de caso na unidade de terapia intensiva neonatal - Costa, Jacira Brasileiro Rodrigues da (2007)
The interpersonal relationships of nursing in hospital organizations are placed in focus of attention in order to find the best quality of the given services. The research related here had as purposes analyze interpersonal relationships in the organization and the interpersonal relationships of nursing at the hospital organization. According to these objectives, it was made a bibliographical revision about two subjects related to people: people in the organizations and people in the hospital organization. Each one of these topics is useful in the construction of a knowledge that helps to understand the subject in a better way. In the empirical phase, the case of a private hospital organization, located in the city of Salvador, was studied. This study was divided into three analytical levels, with basis in the documentary research, in categories of analysis and in social representations. In the first one, the studied hospital organization, its working philosophy, its mission, its values and its administrative structure were the unities of analysis. The second level focused on the characteristics of the Neonatal Intensive Care Unity, considering the philosophy of the given assistance. The third level concentrated on the analysis of the interpersonal relationships of the hospital nursing staff, composed by 34 professionals, 10 nurses and 24 technical nurses. The results suggest that interpersonal relationships are due to other experiences elaborated previously, characterizing a recurrent process. Although exists a awareness about the importance of interpersonal relationship in the result of the quality of the given assistance, it is still missing more social and professional conscience in nursing. The communication process is the main trigger element of other's answer in the interpersonal relationship, and the occurrence of conflicts shows a mismatch between the professional competence over the interpersonal. The responsibility of the nurse goes far beyond his/her technical competence. This responsibility is related to the perception, to the attitude and to the ethical behavior, being this last one a strategic factor in the differentiation of the organization in the labor market. This level of responsibility should be stimulated in academic background, since the interpersonal relationship, the basis of the nursing job process, interferes in the quality of assistance, as well as in the level of satisfaction of the environment and of the staff. It is expected that these results could contribute to a constructive rethink of these relationships in the organizations and in the nursing area.